Dacians, Varangians, Vlachs and The Golden Bough - Bâgiu, Lucian Vasile (Swedish Journal of Romanian Studies, 2025)
The essay interprets four parts of Mihai Sadoveanu’s 1933 enigmatical novel The Golden Bough. The Dacian section focuses on the way geographical, historical, ethnical and social guide marks are introduced to define an uncertain moment in history, the late eighth century in the Carpathians. It also introduces the impetus that must have driven the author to do so and continues with an intertextual comparative reading with Eminescu’s poem The Ghosts, particularly on the depiction of the magus and the unexpected reasons behind the author’s choice, i. e. the Viking pathway. The Varangians segment highlights all seven occurrences of the Northmen collective personage within the story, with minimal historical contextualization of the 787-797 Byzantium, lying before the awkward discrepancy between the Northerners’ enhanced fictional role and the factual inexistence at that particular time and place. The Vlachs fragment presents the six occurrences of “Blacherne” in Sadoveanu’s novel, a documented linguistic and historic speculation of two Romanian scholars on the origin of the exonym “Vlach” as having its source in the Greek milieu of the early Eastern Roman Empire, and the role the Vikings might have played in its spreading, thus proposing an unaccounted-for rationale for the Varangians’ diegetic significance. The Golden Bough division depicts the similarities and the incongruities in comparative readings with Frazer’s anthropological approach and with Virgil’s Aeneid, suggesting a more adequate analogy with the Egyptian hermetic philosophy. The essay ends up with a brief expounding of Sadoveanu’s Masonic status and its likely function in initiating the imaginary Golden Bough.